Bitter friends are not always toxic: The loss of acetic acid bacteria and the absence of Komagataeibacter in the gut microbiota of the polyphagous fly Anastrepha ludens could inhibit its development in Psidium guajava in contrast to A. striata and A. fraterculus that flourish in this host - Ochoa-Sánchez, Manuel; Cerqueda-García, Daniel; Moya, Andrés; Ibarra-Laclette, Enrique; Altúzar-Molina, Alma; Desgarennes, Damaris; Aluja, Martín (Frontiers in Microbiology, 2022)
The gut microbiota is key for the homeostasis of many phytophagous insects, but there are few studies comparing its role on host use by stenophagous or polyphagous frugivores. Guava (Psidium guajava) is a fruit infested in nature by the tephritids Anastrepha striata and A. fraterculus. In contrast, the extremely polyphagous A. ludens only infests guava under artificial conditions, but unlike A. striata and the Mexican A. fraterculus, it infests bitter oranges (Citrus x aurantium). We used these models to analyze whether the gut microbiota could explain the differences in host use observed in these flies. We compared the gut microbiota of the larvae of the three species when they developed in guava and the microbiota of the fruit pulp larvae fed on. We also compared the gut microbiota of A. ludens developing in C. x aurantium with the pulp microbiota of this widely used host. The three flies modified the composition of the host pulp microbiota (i.e., pulp the larvae fed on). We observed a depletion of Acetic Acid Bacteria (AAB) associated with a deleterious phenotype in A. ludens when infesting P. guajava. In contrast, the ability of A. striata and A. fraterculus to infest this fruit is likely associated to a symbiotic interaction with species of the Komagataeibacter genus, which are known to degrade a wide spectrum of tannins and polyphenols. The three flies establish genera specific symbiotic associations with AABs. In the case of A. ludens, the association is with Gluconobacter and Acetobacter, but importantly, it cannot be colonized by Komagataeibacter, a factor likely inhibiting its development in guava.